Performances Analysis of Linear and Circular Microstrip Methods for Determination of Moisture Content in Rubber Latex - Ahmad, Ahmad Fahad (2011)
Following a review of methods for measuring the microwave properties of dielectric materials and moisture measurement methods, majority of the thesis is concerned with the design, construction, and calibration of two different types of microstrip sensors for the determination of moisture content in rubber latex. The Microwave Office 2002 (MWO) was used to design both sensors the linear path and circular ring microstrip lines operating in the frequency range between 2 GHz and 3 GHz which gave the high correlation between dielectric properties and moisture content of latex. S-parameters of the sensors were measured using Professional Network Analyzer (PNA). The microwave properties of interests were attenuation and Q-factor, the main focus of this thesis was to establish the relationship between the microwave properties of the sensors and moisture content in the rubber latex. The actual moisture content was found from standard oven drying method. The theoretical part described the variation in attenuation with frequency for various percentages of moisture content of the sample. The analysis was used to determine the optimum permittivity, width, height and impedance of the microwave substrate for a wide dynamic input range of the sensors. The sensors were fabricated and tested for a range of moisture content. All the sensors were calibrated using standard microwave calibration techniques. Additionally, calibration equations were developed to establish the empirical relationship between the measured attenuation and Q-factors with the actual moisture content. All the results were validated with the actual moisture content. The microstrip ring and line sensor were successfully developed in prediction of moisture content for rubber latex. Both sensors give a different performance in term of sensitivity and mean error. The microstrip line sensor gives a good sensitivity compared to microstrip ring sensor with sensitivity for microstrip linear and microstrip ring sensors are 13.698 %/dB and 3.0697 %/dB respectively. While the microstrip ring sensor gives a smaller mean error compared to microstrip line sensor with mean error for microstrip ring and line sensor are 0.023 and 0.095 respectively.